El procedimiento directo en el Código Orgánico Integral Penal y las limitaciones al derecho a la defensa - Carcelén, Manuel Eduardo (2015)
In this thesis and legal proposal I make a careful analysis of the pros and cons of one of the Special Procedures who have joined with the entry into force of the Code Integral Criminal intended to expedite the form of administering justice in our country. Special procedures found in Article 634 of this legal body. Where classes of Special Procedures are established: 1. Expedited Procedure namely, 2. Direct Method 3. and 4. Process expedited procedure for the Private Practice of Criminal Action. Of these Special Procedures in Article 640 of the Code of Criminal Integral detailed in what the purpose of this Doctrinal and Legal Research consists; The direct method, which albeit is intended to expedite the judicial proceedings in flagrant misdemeanors considered, as its importance is that once carried the Hearing flagrancy a person who has been detained or deprived of their liberty If the judge believes that there is sufficient to determine the guilt of the suspect evidence, must be made within ten days after a single hearing that concentrates all the processes of the criminal trial, where the state of innocence of processing will be ratified or establish the guilty of it. In the same article it states that the tests should be announced up to 3 days before this hearing. Ie the procedural subjects in the best have seven days to announce test, while I consider too short and that ultimately affects albeit both parties, primarily affects the constitutional right to defense states that it should have enough time to prepare this time, which is referred to in paragraph b 76.numeral Article 7 of the Constitution of the Republic of Ecuador and also is one of the legal guarantees provided for in Article 8 paragraph 2 letter c, of the American Convention on Human Rights which states in relevant part attaches to adequate time and means for their defense. Thus, I am convinced that the principle of procedural privileging Celerity can not or should affect neither effective remedy due process in relation to the right to defense, with a summary Pending such as direct judgment, as is currently happening